Energy management for self - sustainable building - Lee, Nicholas Wen Feng (2015)
Monitoring an energy management system can be a chore when there is a need to be physically present to view the data. Time is of essence and it would be great if the data collected can be viewed at the user’s convenience. Hence, this project focuses on implementing a cloud environment so as to make the data collected available for viewing through the cloud. This can not only help save users’ time but also allows users to monitor the data as and when they like to without any time restriction. For this project, the services provided by Amazon Web Services were called upon. The two services that were used were the Amazon Elastic Compute Cloud and the Amazon Relational Database Service. The former provides the cloud to work in while the latter provides the database to store the data. Both Java and PHP were used in conjunction with the editor Eclipse in an attempt to transfer data collected through LabVIEW into the Amazon database. MySQL Workbench, a visual toolkit for reading data in a MySQL database, was used in this project to see if it allows the viewing of the data collected in the cloud. The combination of the aforementioned software allowed the completion of the project. Codes are required in order to transfer the data collected into the Amazon database and Eclipse was used to key in the codes. MySQL Workbench allows the viewing of the data through the cloud. This would certainly help make the monitoring of an energy management system easier. Also this improves efficiency because the data can now be viewed at the users’ convenience once they have access to the cloud.